Bimetal ion co-doped zinc oxide nano-powder and preparation method thereof
The preparation of bimetal ion co-doped zinc oxide nano powders through prepolymerization-pyrolysis has solved the problems of high cost and complex process in the prior art preparation method, and achieved high purity and excellent electrical properties of nano powders, which are suitable for industrial production.
Patent Information
- Application Number
- CN202510032819.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
AI Technical Summary
In the prior art, the preparation method of bimetal ion co-doped ZnO has high cost, complex process and low crystallinity of products, which is not suitable for industrial applications.
Bimetal ion co-doped zinc oxide nanopowder was prepared by prepolymerization-pyrolysis. The nanopowder was obtained by dissolving zinc, gallium and aluminum metal salts in an aqueous unsaturated carboxylic acid solution respectively, and after prepolymerization, the nanopowder was obtained by pyrolysis.
The high purity and excellent electrical properties of bimetal ion-co-doped zinc oxide nano powder are achieved, suitable for large-scale production and reduce production costs.
Smart Images

Figure CN119822398A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of zinc oxide-doped nano material preparation, and particularly relates to a double metal ion co-doped zinc oxide nano powder and a preparation method thereof. Background Art
[0002] Transparent conductive oxide (TCO) films have many uses in modern electronic devices, especially as key components of touch screens, flat panel displays, solar cells, smart windows, and organic light-emitting diodes (OLEDs). Indium tin oxide (ITO) is the current industry standard TCO material for such devices because of its high optical transparency (>80%) and low resistivity (10 - 4 cm level), but due to the high cost and increasing scarcity of indium, people are exploring other more sustainable, non-toxic and cheap TCO materials as potential substitutes for ITO. ZnO crystal has a hexagonal zincite structure and is a wide bandgap (~3.37eV) and highly transparent n-type semiconductor. The presence of excess free electrons in the ZnO crystal structure improves the conductivity of ZnO. By doping metals into the zinc oxide lattice, the bandgap energy of the semiconductor can be effectively reduced to enhance its photoelectric properties. At present, the two most widely studied dopants in the zinc oxide doping system are aluminum (Al 3+ ) and gallium (Ga 3+ ), the ionization energy of Group III elements such as Al and Ga is lower than that of Group II elements such as Zn. When replacing Zn in the ZnO crystal structure 2+ When Ga is added, it can provide extra electrons, thereby greatly improving the conductivity of ZnO. At the same time, the Fermi level enters the conduction band of ZnO, its bandgap width is reduced, and the optical properties are enhanced. Compared with AZO, GZO has low reactivity and good oxidation resistance; Al is easily oxidized and has lower thermal stability than Ga; and GZO has lower approximate durability in humid environments, and its crystal structure distortion is smaller than AZO. Therefore, compared with other dopants, it has potential superior stability, but the preparation cost of doping Ga is higher. And under the condition of single element doping, the performance improvement of ZnO material has a certain limit, so the use of double metal ions or multi-metal ions co-doped ZnO can provide more possibilities for high-performance TCO materials, and can better balance the chemical stability, electrical and optical properties and cost of ZnO-based conductive materials.
[0003] At present, there are still few preparation methods for double metal ion co-doped ZnO. Most of them use hydrothermal method, ion implantation method, chemical vapor deposition method and other methods. There are problems such as high cost, complicated process, low product crystallinity and unsuitability for industrial application. It is urgent to develop a preparation method for double metal ion co-doped ZnO nanopowder suitable for large-scale production. Breakthroughs in this area will be conducive to the manufacture of high-quality ZnO-based target materials and the subsequent development of TCO thin film industry. Summary of the invention
[0004] The purpose of the present invention is to provide a double metal ion co-doped zinc oxide nanopowder and a preparation method thereof to solve the problems existing in the above-mentioned prior art. The present invention prepares the double metal ion co-doped zinc oxide nanopowder by a prepolymerization-pyrolysis method, the preparation method is simple, the reaction rate is fast, and it is suitable for large-scale production. The prepared doped zinc oxide nanopowder has high purity and excellent electrical properties.
[0005] One of the technical solutions provided by the present invention:
[0006] A double metal ion co-doped zinc oxide nanopowder, the double metal ion co-doped zinc oxide nanopowder includes two different metal ion dopings at the same time, and its chemical formula is Zn (1-x-y) M1 x M2 y O, wherein 0.005<x<0.05, 0.005<y<0.05, wherein M1 is a gallium ion and M2 is an aluminum ion, or M1 is an aluminum ion and M2 is a gallium ion.
[0007] Preferably, the double metal ion co-doped zinc oxide nanopowder is composed of nano-flaky particles, and the thickness of the nano-flaky particles is 20-100 nm. This form of nanopowder is conducive to the sintering of the final coating target material and is easy to form a relatively dense target material.
[0008] The second technical solution provided by the present invention is:
[0009] A method for preparing the above-mentioned double metal ion co-doped zinc oxide nanopowder comprises the following steps: respectively adding zinc salt, gallium salt and aluminum salt to an unsaturated carboxylic acid aqueous solution to obtain a zinc precursor solution, a gallium precursor solution and an aluminum precursor solution, continuously stirring the zinc precursor solution in a water bath, synchronously dropping the gallium precursor solution, the aluminum precursor solution and a polymerizer into the zinc precursor solution to obtain a prepolymerization reaction solution, continuing to stir in a water bath, obtaining a colloidal solution through a polymerization reaction, obtaining a colloid after drying, and performing pyrolysis treatment, cooling to room temperature, and grinding to obtain the double metal ion co-doped zinc oxide nanopowder.
[0010] Preferably, the molar ratio of Al, Ga and Zn metal ions in the prepolymerization reaction solution is (0.005-0.05): (0.005-0.05): (0.9-0.99).
[0011] Preferably, the polymerization agent is selected from sodium persulfate or ammonium persulfate, and the amount of the polymerization agent added is 1-5% of the total mass of the zinc precursor solution, the gallium precursor solution and the aluminum precursor solution.
[0012] As a strong oxidizing polymerization agent, sodium sulfate or ammonium persulfate plays the role of initiating the polymerization reaction in the present invention. The polymerization agent, gallium precursor solution and aluminum precursor solution are simultaneously dripped into the zinc precursor solution, and the network polymerization degree is continuously increased during the mixing of solution ions, so that gallium and aluminum ions are fixed in the zinc molecular network, avoiding the phenomenon of inability to co-dope due to ion priority reaction.
[0013] The zinc salt, gallium salt and aluminum salt include acetate, phosphate and nitrate, preferably nitrate.
[0014] Preferably, the unsaturated carboxylic acid includes one or more of acrylic acid, methacrylic acid and propiolic acid, and the mass fraction of the unsaturated carboxylic acid aqueous solution is 20-30%.
[0015] Preferably, the temperature of the continuous stirring in the water bath and the continued stirring in the water bath are both 30 to 50° C., and the time of the continued stirring in the water bath is 30 to 60 minutes.
[0016] Preferably, the polymerization reaction temperature is 60-100° C. and the time is 10-120 min.
[0017] Preferably, the drying temperature is 70-100° C., and the drying time is 2-12 h; more preferably, the drying temperature is 80° C., and the drying time is 3 h.
[0018] Preferably, the pyrolysis treatment is to heat up to 500-700°C at a rate of 5-10°C / min and then keep the temperature for 2-6 hours. More preferably, the pyrolysis treatment is to heat up to 600°C at a rate of 10°C / min and then keep the temperature for 2 hours.
[0019] Compared with the prior art, the present invention has the following advantages and technical effects:
[0020] The prepolymerization-pyrolysis method adopted in the preparation method provided by the present invention solves the problem that it is difficult to co-dope multiple ions due to the difference in reaction activity when co-doping. It is simple to operate, the reaction process is easy to control, the polymerization rate is fast and no by-products are generated. The prepared double metal ion co-doped zinc oxide nanopowder has uniform composition and high purity. The preparation method provided by the present invention has low raw material cost, high output, high process adaptability, and is suitable for large-scale industrial production; the preparation method provided by the present invention can accurately control the doping amount of different metal ions in zinc oxide crystals, and has better performance than aluminum or gallium single metal doping, which can reduce production costs and improve the relevant performance of doped ZnO-based materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0022] Figure 1 XRD patterns of aluminum-gallium bimetallic ion co-doped zinc oxide nanopowders prepared in Example 1 (Case 1) and Example 2 (Case 2);
[0023] Figure 2 This is the SEM spectrum of the aluminum-gallium dual metal ion co-doped zinc oxide nanopowder prepared in Example 1, wherein a is a SEM spectrum magnified 10,000 times, and b is a SEM spectrum magnified 30,000 times.
[0024] Figure 3 The SEM spectra of the aluminum-gallium bimetallic ion co-doped zinc oxide nanopowder prepared in Comparative Example 1, wherein a is a SEM spectrum magnified 10,000 times, and b is a SEM spectrum magnified 30,000 times;
[0025] Figure 4 The XPS spectra of Zn and Ga elements of the aluminum-gallium bimetallic ion co-doped zinc oxide nanopowder prepared in Comparative Example 1, wherein (a) is the Zn 2p orbital XPS spectrum, and (b) is the Ga 2p orbital XPS spectrum. DETAILED DESCRIPTION
[0026] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0027] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0028] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0029] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0030] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0031] The embodiment of the present invention provides a method for preparing a bimetallic ion co-doped zinc oxide nanopowder, wherein zinc, gallium and aluminum metal salts are respectively dissolved in an unsaturated carboxylic acid aqueous solution, and stirred evenly to form a precursor liquid; then, under magnetic stirring in a water bath at 30 to 50°C, the gallium and aluminum precursor solutions are simultaneously and slowly added dropwise to the zinc precursor solution with a sodium persulfate or ammonium persulfate polymerization agent, and a prepolymerization reaction solution is formed after sufficient stirring; the prepolymerization reaction solution is then heated to 60 to 100°C to undergo a sufficient polymerization reaction, and a colloidal solution is obtained after the reaction is completed; the colloidal solution is then dried, and then placed in a muffle furnace for pyrolysis treatment to obtain a bimetallic ion co-doped zinc oxide nanopowder. The present invention adopts a prepolymerization-pyrolysis method to prepare a bimetallic ion co-doped zinc oxide nanopowder, and the properties of the doped zinc oxide nanopowder can be regulated over a large range by controlling the proportion and content of the doped metal ions. The prepared aluminum-gallium co-doped zinc oxide nanopowder can be used to manufacture coating targets, and is suitable for the application of high-performance conductive film coating materials.
[0032] Example 1 A method for preparing double metal ion co-doped zinc oxide nanopowder
[0033] 0.025 mol of zinc acetate was weighed and added to 50 g of 30% methacrylic acid aqueous solution and stirred for 20 min to form a zinc precursor solution; 0.001 mol of gallium nitrate was added to 5 g of 30% methacrylic acid aqueous solution and stirred evenly to form a gallium precursor solution; 0.0005 mol of aluminum nitrate was added to 5 g of 30% methacrylic acid aqueous solution and stirred evenly to form an aluminum precursor solution; at the same time, 5 g of 5% sodium persulfate aqueous solution was prepared; then, the zinc precursor solution was placed in a 40°C water bath and continuously stirred by magnetic force; three constant pressure drops were used to A gallium precursor solution, an aluminum precursor solution and a sodium persulfate aqueous solution are simultaneously and slowly dripped into the stirred zinc precursor solution using a liquid funnel; after the addition is completed, the stirring in a water bath is continued for 30 minutes; then, the water bath temperature is increased to 90°C to induce a polymerization reaction, and a colloidal solution is obtained after the reaction for 30 minutes; the colloidal solution is placed in a drying oven and dried at 80°C for 3 hours; the dried colloid is placed in a muffle furnace, and the temperature is increased to 600°C at a heating rate of 10°C / min, and the heat preservation time is 2 hours, and the colloid is cooled with the furnace. After grinding and annealing, the sample is obtained to obtain a double metal ion co-doped zinc oxide nanopowder, in which the Al:Ga molar ratio is close to 1:1.
[0034] Example 2 A method for preparing double metal ion co-doped zinc oxide nanopowder
[0035] 0.025 mol of zinc acetate was weighed and added to 50 g of 30% methacrylic acid aqueous solution, and stirred for 20 min to form a zinc precursor solution; 0.001 mol of gallium nitrate was added to 5 g of 30% methacrylic acid aqueous solution and stirred evenly to form a gallium precursor solution; 0.001 mol of aluminum nitrate was added to 5 g of 30% methacrylic acid aqueous solution and stirred evenly to form an aluminum precursor solution; at the same time, 5 g of 3% ammonium persulfate aqueous solution was prepared; then, the zinc precursor solution was placed in a 45°C water bath and continuously stirred by magnetic force; three constant pressure dripping A gallium precursor solution, an aluminum precursor solution and an ammonium persulfate aqueous solution are simultaneously and slowly dripped into the stirred zinc precursor solution using a funnel; after the addition is completed, stirring in a water bath is continued for 30 minutes; then, the water bath temperature is increased to 80°C to induce a polymerization reaction, and a colloidal solution is obtained after the reaction for 20 minutes; the colloidal solution is placed in a drying oven and dried at 100°C for 3 hours; the dried colloid is placed in a muffle furnace, and the temperature is increased to 650°C at a heating rate of 5°C / min, and the heat preservation time is 2 hours, and the colloid is cooled with the furnace. After grinding and annealing, the sample is obtained to obtain a double metal ion co-doped zinc oxide nanopowder, wherein the Al:Ga molar ratio is about 1:0.6.
[0036] Figure 1The XRD patterns of the aluminum-gallium bimetallic ion co-doped zinc oxide nanopowders prepared in Example 1 (Case 1) and Example 2 (Case 2) are shown in Table 1. Figure 1 It can be seen that both products have the wurtzite ZnO crystal structure.
[0037] Figure 2 The SEM spectra of the aluminum-gallium dual metal ion co-doped zinc oxide nanopowder prepared in Example 1, wherein a is a SEM spectrum magnified 10,000 times, and b is a SEM spectrum magnified 30,000 times. Figure 2 The specific morphology and size of the nanopowder can be seen in the figure.
[0038] Table 1 shows the ICP test results of the aluminum-gallium dual metal ion co-doped zinc oxide nanopowder prepared in Example 1, indicating that the aluminum-gallium content therein is about 1%, and the ratio of the two is close to 1:1.
[0039] Table 1
[0040]
[0041] Comparative Example 1
[0042] 0.025 mol of zinc acetate was weighed and added to 50 g of a 30% aqueous methacrylic acid solution, and stirred for 20 min to form a zinc precursor solution; 0.001 mol of gallium nitrate was added to 5 g of a 30% aqueous methacrylic acid solution, and stirred evenly to form a gallium precursor solution; 0.0005 mol of aluminum nitrate was added to 5 g of a 30% aqueous methacrylic acid solution, and stirred evenly to form an aluminum precursor solution; at the same time, 5 g of a 5% aqueous sodium persulfate solution was prepared; then, the zinc precursor solution was placed in a 40°C water bath, and magnetic stirring was continued; the gallium precursor solution, the aluminum precursor solution, and the sodium persulfate solution were placed in a 40°C water bath, respectively. Using three constant-pressure dropping funnels, the gallium precursor solution and the aluminum precursor solution are simultaneously and slowly dripped into the stirred zinc precursor solution, and then the sodium persulfate aqueous solution is slowly dripped into the stirred mixed solution of the zinc precursor solution, the gallium precursor solution and the aluminum precursor solution; after the dropwise addition is completed, the water bath is continued to be stirred for 30 minutes; then, the water bath temperature is increased to 90°C to induce a polymerization reaction, and a colloidal solution is obtained after the reaction for 30 minutes; the colloidal solution is placed in a drying oven and dried at 80°C for 3 hours; the dried colloid is placed in a muffle furnace, and the temperature is increased to 600°C at a heating rate of 10°C / min, the heat preservation time is 2 hours, and the sample is cooled with the furnace, and the gallium-doped zinc oxide nanopowder is obtained after grinding and annealing.
[0043] Figure 3 The SEM images of the gallium co-doped zinc oxide nanopowder prepared in Comparative Example 1, wherein a is a SEM image magnified 10,000 times, and b is a SEM image magnified 30,000 times. Figure 4 It can be found that the powder is obviously agglomerated and the size is obviously non-uniform compared with Example 1.
[0044] Figure 4 The XPS graphs of the gallium co-doped zinc oxide nanopowder prepared in Comparative Example 1, wherein (a) is the XPS spectrum of the Zn 2p orbital, and (b) is the XPS spectrum of the Ga 2p orbital, indicating that the method provided in Comparative Example 1 is used to prepare the doped ZnO, Al 3+ with Ga 3+ Under ion competition, Ga preferentially enters the ZnO lattice.
[0045] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A double metal ion co-doped zinc oxide nanopowder, characterized in that: The double metal ion co-doped zinc oxide nanopowder includes two different metal ion dopings, and its chemical formula is Zn (1-x-y) M1 x M2 y O, wherein 0.005<x<0.05, 0.005<y<0.05, wherein M1 is a gallium ion and M2 is an aluminum ion, or M1 is an aluminum ion and M2 is a gallium ion.
2. The double metal ion co-doped zinc oxide nanopowder according to claim 1, characterized in that: The double metal ion co-doped zinc oxide nano powder is composed of nano flaky particles, and the thickness of the nano flaky particles is 20-100 nm.
3. A method for preparing the double metal ion co-doped zinc oxide nanopowder according to claim 1 or 2, characterized in that: The following steps are involved: A zinc salt, a gallium salt and an aluminum salt are respectively added to an unsaturated carboxylic acid aqueous solution to obtain a zinc precursor solution, a gallium precursor solution and an aluminum precursor solution; the zinc precursor solution is continuously stirred in a water bath; the gallium precursor solution, the aluminum precursor solution and a polymerizing agent are simultaneously dropped into the zinc precursor solution to obtain a prepolymerization reaction solution; the water bath is continuously stirred to obtain a colloidal solution through a polymerization reaction; a colloid is obtained after drying; the colloid is subjected to pyrolysis treatment, cooled to room temperature, and ground to obtain the bimetallic ion co-doped zinc oxide nanopowder.
4. The preparation method according to claim 3, characterized in that: The molar ratio of Al, Ga and Zn metal ions in the prepolymerization reaction solution is (0.005-0.05): (0.005-0.05): (0.9-0.99).
5. The preparation method according to claim 3, characterized in that: The polymerizing agent is selected from sodium persulfate or ammonium persulfate, and the added amount of the polymerizing agent is 1-5% of the total mass of the zinc precursor solution, the gallium precursor solution and the aluminum precursor solution.
6. The preparation method according to claim 3, characterized in that: The unsaturated carboxylic acid comprises one or more of acrylic acid, methacrylic acid and propiolic acid, and the mass fraction of the unsaturated carboxylic acid aqueous solution is 20-30%.
7. The preparation method according to claim 3, characterized in that: The temperature of the continuous stirring in the water bath and the continued stirring in the water bath are both 30 to 50° C., and the time of the continued stirring in the water bath is 30 to 60 minutes.
8. The preparation method according to claim 3, characterized in that: The polymerization reaction temperature is 60-100° C. and the reaction time is 10-120 min.
9. The preparation method according to claim 3, characterized in that: The drying temperature is 70-100° C. and the drying time is 2-12 hours.
10. The preparation method according to claim 3, characterized in that: The pyrolysis treatment is to increase the temperature to 500-700° C. at a rate of 5-10° C. / min and then keep the temperature for 2-6 hours.
Citation Information
Patent Citations
Method for preparing n-type doped zinc oxide nanometer powder
CN101665235A
Aluminum-gallium co-doping zinc oxide nano-powder and preparation method for high intensity high conductivity sputtering coating target material thereof
CN103408062A
Co-doped conductive oxidation powder material and preparation method thereof
CN103818946A